PRINCIPAL'S LEADERSHIP IN DEVELOPING TEACHER PROFESSIONALISM - Ina Marlina Lubis; Hasan Maksum; Wawan Purwanto (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The principal as a leader in the school is required to have creativity, motivational leadership, and effective leadership so that he can mobilize all teachers according to their roles and functions effectively and efficiently. The principal is the sole leader in the school who has the responsibility and authority to regulate, manage and organize activities in the school, so that what is the goal of the school can be achieved. The principal should be a visionary, namely able to look forward to the life of the Indonesian people with all its opportunities and challenges. In short, the principal must be able to project the abilities and competencies as well as the leadership style needed by subordinates and the community. So that they are required to be able to apply their leadership styles that can reflect behaviors that can be imitated by their subordinates and can motivate the work of teachers and staff they lead.